PROJECT-BASED LEARNING AS TEACHING MODEL OF CONGRATULATION CARDS: HOW IT IMPROVES WRITING ABILITY - Munadhiroh, Siti; Egar, Ngasbun; Prastikawati, Entika Fani (JP3 (Jurnal Pendidikan dan Profesi Pendidik), 2025)
The English teaching and learning using modern and real-world experience learning models will provide important benefits related to written and spoken communication. The writing definition is a means of communicating a form of interpersonal as a writer shares his ideas and thinks with reviewers through textual mimicking. The approach of Project-based learning has been demonstrated to have the possibility to enhance students' thinking critically, how communication, and creatively in teamwork. This was study established to investigate the implementation of Project-based learning to improve students’ writing ability in congratulation cards. This study was conducted utilizing a method of quantitative connection with the design of quasi-experimental. Standards of design quasi is the study used two classes as the class of control and class of experiment. Class of control was learned using conventional learning and the experiment group was taught using Project-based Learning. The findings revealed that the students in the class of control had less enthusiasm for learning. The experiment class experienced in the classroom activity is intended to be highly involved. The students are more attracted to working in groups and interactive classes. The model of Project-based learning is suitable to apply in the classroom for teachers and students in writing class especially related to the congratulation card material. Project-based learning is a good choice if students need to group tasks, sharpen critical thinking skills, freedom to generate their ideas, and create a more active classroom atmosphere especially to improve their writing ability.